Impact of the COVID-19 Outbreak on Pakistan’s Financial Indicators - MUHAMMAD ASIF KHAN; Muhammad Siddiq; Zahid Sarwar (Journal of Business & Tourism, 2023)
Across the globe, the financial and health system of the developing and developed countries is shattered by the novel coronavirus COVID-19 since its outbreak. It has affected the financial system of all the countries but has severe consequences on less developed and weak financial system countries. This study investigated the impact of the novel COVID-19 on different sectors concerning the Pakistan economy.This research investigated the impact of COVID-19 on Pakistan Stock Exchange, gold rate, interest rate and exchange rates. The time period used for data analysis was from 27th February 2020 to 31st March 2020. The outcome confirms that Pakistan stock is severely hit by the COVID-19 and showing the decline in their 100 index and total share index. The results also revealed that the gold rate and exchange rate showed a rapid increase in their prices. This epidemic has devalued the Pakistan rupees from 154 to 166 and showing a decline. The gold rate is also affected by this epidemic and showing an increase in their rates. The results show that the government is taking action to provide some facilities to different sectors to cope with the outbreak, and it will stabilize the financial system in the country.